The balance between fetal oxytocin and placental leucine aminopeptidase (P-LAP) controls human uterine contraction around labor onset - Masato Yoshihara; Shigehiko Mizutani; Kunio Matsumoto; Yukio Kato; Yusuke Masuo; Arita Harumasa; Shohei Iyoshi; Sho Tano; Hidesuke Mizutani; Tomomi Kotani; Eita Mizutani; Kiyosumi Shibata; et al. (Elsevier, 2023)
A fetal pituitary hormone, oxytocin which causes uterine contractions, increases throughout gestation, and its increase reaches 10-fold from week 32 afterward. Oxytocin is, on the other hand, degraded by placental leucine aminopeptidase (P-LAP) which exists in both terminal villi and maternal blood. Maternal blood P-LAP increases with advancing gestation under the control of non-genomic effects of progesterone, which is also produced from the placenta. Progesterone is converted to estrogen by CYP17A1 localized in the fetal adrenal gland and placenta at term. The higher oxytocin concentrations in the fetus than in the mother demonstrate not only fetal oxytocin production but also its degradation and/or inhibition of leakage from fetus to mother by P-LAP. Until labor onset, the pregnant uterus is quiescent possibly due to the balance between increasing fetal oxytocin and P-LAP under control of progesterone. A close correlation exists between the feto-placental and maternal units in the placental circulation, although the blood in the two circulations does not necessarily mix. Fetal maturation results in progesterone withdrawal via the CYP17A1 activation accompanied with fetal oxytocin increase. Contribution of fetal oxytocin to labor onset has been acknowledged through the recognition that the effect of fetal oxytocin in the maternal blood is strictly regulated by its degradation by P-LAP under the control of non-genomic effects of progesterone. In all senses, the fetus necessarily takes the initiative in labor onset.